Workbook on oral biology / Khor Goot Heah ... [et al.] - Jamil, Kazi Ahsan; Younis, Luay Thanoon; Said Gulam Khan, Hasnah Begum; Khor, Goot Heah (UiTM Press, 2022)
Oral Biology is about the nature of oral and craniofacial tissues and its application of basic scientific knowledge of oral tissues in health and disease. Thus, this Workbook on Oral Biology is specifically targeted for undergraduate students learning oral biology in any dental, medical, or allied health courses, for their better understanding in the related topics. This workbook contains basic topics of oral biology which are covering oral craniofacial structures, chemical composition of teeth, oral flora, oral environment, and the structural and functional relationship of oral tissues. Practical sessions will emphasize on topics which need to be reinforced by demonstration and hands-on. This includes draw what they see by looking at the histological sections using microscopes or virtual resources, understand the demonstrations shown on videos, carrying out wet experiments and analyse data. Tutorials are also included in the workbook to reinforce students' understanding during the gathering process of knowledge. This workbook provides a brief overview of oral biology that might not only be valuable to undergraduates of dentistry and medicine but also to allied health. In addition, it also contributes as an added value to the body of the knowledge in oral biology.